Efektivitas Kompres Hangat dan Kompres Hydrogel On Polyacrylate-Basis (Kompres Plester) terhadap Penurunan Suhu Tubuh Anak Hipertermia Usia 0-5 Tahun - Alvionita, Ajeng Merlydia; Herliana, Irma (Journal of Nursing Education and Practice, 2023)
Introduction: Hyperthermia is a condition of body temperature higher than normal or temperature above normal. Hyperthermia generally occurs when a person experiences health problems that become a problem in children aged 0-5 years. Objectives: This study aims to determine the effectiveness of warm compresses and hydrogel compresses on polyacrylate-base (plaster compresses) against reducing body temperature of hyperthermic children aged 0-5 years. Method: This research uses a type of quasi-experimental research with two groups, pre-test and post-test design. Researchers grouped respondents into two groups, one group was given a warm compress intervention, and the other group was given a hydrogel compress intervention on polyacrylate-based (plaster compress) made by a manufacturer. Each group had their body temperature measured both before being given the intervention and after being given the intervention. The total sample was 32 children aged 0-5 years, the sampling technique was purposive sampling. The data analysis used in this research was univariate and bivariate using a parried simple t-test.    Result: The results found that based on the analysis of the effectiveness of warm compresses and hydrogel compresses on polyacrylate-basis (plaster compresses) on reducing body temperature of children aged 0-5 years, it was found that the effectiveness of warm compresses was as much as the male sex (56.3%) and the rest of the female sex (43.8%). It was found that the effectiveness of hydrogel compresses on polyacrylate-base (plaster compresses) was as much as the male sex (58.8%) and the rest of the female sex (31.1%). The difference in the effectiveness of warm compresses and hydrogel in polyacrylate-based plaster compresses in reducing hyperthermia temperature with a p-value of 0.001. Conclusion: There is a difference in the effectiveness of warm compresses and Hydrogel on polyacrylate-basis plaster compresses against hyperthermia temperature reduction.